2015
DOI: 10.1542/peds.2014-2967
|View full text |Cite|
|
Sign up to set email alerts
|

Etiologies of NICU Deaths

Abstract: BACKGROUND AND OBJECTIVES: Infant mortality is an indicator of overall societal health, and a significant proportion of infant deaths occur in NICUs. The objectives were to identify causes of death and to define potentially preventable factors associated with death as areas for quality improvement efforts in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 8 publications
4
82
2
Order By: Relevance
“…Similar result was described by Katz et al from Sarlahi district of Nepal. 10 Death rates for an inborn and outborn neonate was similar in our study. Earlier study by Hedstrom et al from Uganda's neonatal center found two times more risk of mortality in outborn neonates.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar result was described by Katz et al from Sarlahi district of Nepal. 10 Death rates for an inborn and outborn neonate was similar in our study. Earlier study by Hedstrom et al from Uganda's neonatal center found two times more risk of mortality in outborn neonates.…”
Section: Discussionsupporting
confidence: 83%
“…[5][6][7][8][9] In the developed countries genetic or structural anomalies is major cause of poor outcome. 10 Most of the neonatal deaths occur in the first week of life.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the proportions of deaths due to congenital anomalies (n=4, 4.1%) included tracheal stenosis, multiple dysmorphic feathures without definite diagnosis and cyanotic heart anomalies were relatively lower than those reported in other studies 6,25,31) , likely because infants who required cardiac or abdominal surgery were transferred to other hospitals due to a lack of professional manpower in our unit. There were 99 cases who were transferred to other hospitals over the 13-year period studied, mainly because of abdominal operations for congenital gastrointestinal obstruction or NEC (n=43), and cardiac manage ment for suspected congenital heart defects (n=24).…”
Section: Discussioncontrasting
confidence: 72%
“…Although advanced medical care over recent decades has resulted in significantly improved neonatal outcomes [1][2][3][4] , neonatal mortality still represents a large proportion of overall infant and childhood mortality. Under standing the causes and trends of deaths in neonatal intensive care units (NICUs) is important because the proportion of postneonatal deaths has a major impact on infant mortality 5,6) . Prematurity remains one of the major causes of neonatal death [7][8][9] , but there have been important changes in the specific causes of neonatal mortality [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…NEC becomes a larger proportionate cause of mortality as GA increases, particularly at 26-27wk GA. In addition, data from a prospective study in 46 US neonatal intensive care units (NICU) found NEC to be the second most common cause of death among all infants (term and preterm) born at ≥22wk GA, accounting for 10% of NICU deaths 22 . Only deaths due to extreme prematurity were more common, accounting for 14% of all NICU deaths.…”
Section: Survivalmentioning
confidence: 99%